HUBUNGAN AKSEPTOR KB IUD DENGAN KEJADIAN KEPUTIHAN DI PUSKESMAS JETIS KOTA YOGYAKARTA - Mayangsari, Rr Nindya; Saidah, Siti; Lidia, Besse (Jurnal Kebidanan Mutiara Mahakam, 2019)
The implementation of the Family Planning (KB) program in Indonesia raisesvarious problems in the health sector which are generally experienced by many women.One of the problems faced by women in line with the dissemination of this program inIndonesia is the emergence of vaginal problems in the use of Intra-Uterine Device (IUD)contraception. Leucorrhoea is abnormal vaginal secretion in women, the longer the useof an IUD, the more at risk of developing vaginal discharge. This study aims to study andanalyze the relationship between IUD KB acceptors and vaginal discharge. The researchdesign used was an observational method with a cross sectional study design. Sample sizewas 92 patients. The sample used was patients aged 18-60 years who sufferedleucorrhoea at the Jetis Primary Health Center, Yogyakarta City. Sampling usingpurposive sampling technique. The relationship between intra-uterine devicecontraceptive acceptors and vaginal discharge was analyzed using Chi-Square using theSPSS version 21.0 for Windows program. There was a statistically significant associationof patients using intra-uterine device contraception and experiencing vaginal dischargetotaling 43 people (46.7%) and 12 people who did not experience vaginal discharge(13.1%). While patients who did not use intra-uterine device contraception and hadvaginal discharge were 21 people (22.8%) and those who did not suffer from vaginaldischarge were 16 people (17.4%). The Chi-square hypothesis test results obtainedsignificance 0.029 where p <0.05. There is a relationship between intra-uterine devicecontraceptive acceptors and the incidence of vaginal discharge in the Jetis PrimaryHealth Center in Yogyakarta which is statistically significant.